La mère des fils de Zébédée - Manns, Frédéric (Liber annuus, 2017)
Jewish women were extremely instrumental at the most critical moments of Christian history. This article discusses how the Synoptic Gospels report on the question of precedence among Jesus' disciples. The Lucan version which is reported in another context is only mentioned here. Can the mother of the Zebedee brothers depicted by Matthew be compared to other mothers known to us from Jewish literature? Can this comparison teach us either about the author of Matthew or add to our understanding of the social models and tendencies in Matthew?